2010
DOI: 10.1186/1471-2229-10-259
|View full text |Cite
|
Sign up to set email alerts
|

Does epigenetic polymorphism contribute to phenotypic variances in Jatropha curcas L.?

Abstract: BackgroundThere is a growing interest in Jatropha curcas L. (jatropha) as a biodiesel feedstock plant. Variations in its morphology and seed productivity have been well documented. However, there is the lack of systematic comparative evaluation of distinct collections under same climate and agronomic practices. With the several reports on low genetic diversity in jatropha collections, there is uncertainty on genetic contribution to jatropha morphology.ResultIn this study, five populations of jatropha plants co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 21 publications
4
55
0
Order By: Relevance
“…Four T0 trees with high oleic acid trait (oleic acid content > 70% of total fatty acid in T1 seed, including X8#34 and X8#291), 16 T0 transgenic trees with non-high oleic acid and two control wild-type Jc -MD plants were monitored for the following agronomic traits: plant height, number of primary branches after one trimming, diameter of main stem, seed number per fruit and seed number per tree after transplanting (September 2009 to June 2011). Previous studies have shown that Jc -MD was the earliest to flower and the most productive cultivar in field trials [17]. Under our greenhouse conditions, it took almost one year to flower and there was an average of 12 seeds per tree with an average seed weight of 330 mg, which was comparable to T0 high oleic plants and T0 non-high oleic plants as shown in Table 1.…”
Section: Resultssupporting
confidence: 50%
“…Four T0 trees with high oleic acid trait (oleic acid content > 70% of total fatty acid in T1 seed, including X8#34 and X8#291), 16 T0 transgenic trees with non-high oleic acid and two control wild-type Jc -MD plants were monitored for the following agronomic traits: plant height, number of primary branches after one trimming, diameter of main stem, seed number per fruit and seed number per tree after transplanting (September 2009 to June 2011). Previous studies have shown that Jc -MD was the earliest to flower and the most productive cultivar in field trials [17]. Under our greenhouse conditions, it took almost one year to flower and there was an average of 12 seeds per tree with an average seed weight of 330 mg, which was comparable to T0 high oleic plants and T0 non-high oleic plants as shown in Table 1.…”
Section: Resultssupporting
confidence: 50%
“…Contrary to marker-based approaches, high performance liquid chromatography (HPLC) has been applied in studies of DNA methylation of plants regenerated via tissue culture (Renau-Morata et al 2005;Rival et al 2013). This technique supports general information on global DNA methylation and could be applied for the evaluation of differences among plant materials that could be related to spontaneously arising off-type plants (Johannes et al 2009;Yi et al 2010).…”
Section: Introductionmentioning
confidence: 57%
“…In a similar study on 72 J. curcas accessions representing 13 countries, biochemical composition analysis of seeds showed wide variation in seed kernel crude protein, oil content, ash content and phorbol ester (PE) in seed [12]. Similarly, a two year progeny field trial conducted in Singapore with accessions from India, Indonesia, China, Africa and South America found significant variability in 1 year and 2 year accumulated seed yield, plant height at 2 year, number of primary branches, number of flowering branches, dormancy during drought period, time from seed sowing to first flowering as well as seed oil content [13]. For commercial plantation, there is the urgent need for improvement towards higher seed productivity and better uniformity in field.…”
Section: Introductionmentioning
confidence: 98%